2024
DOI: 10.1002/ejsc.12077
|View full text |Cite
|
Sign up to set email alerts
|

The intensity rather than the quantity of prior work determines the subsequent downward shift in the power duration relationship in professional cyclists

James Spragg,
Peter Leo,
Andrea Giorgi
et al.

Abstract: To determine whether the intensity of prior work is an important contributing factor to the downward shift in the power‐duration relationship. Data were collected from 14 professional cyclists (height 176.3 cm ± 7, body mass 67.3 kg ± 5, CP, 5.3 W·kg−1 ± 0.21). Participants conducted a power profile test three times consisting of a 15s, a 3 min and a 12 min maximal effort trial utilizing a standardized climb. On the first occasion, the power profile test was conducted in a fresh state (Fresh), the subsequent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…When compared to exercise performed at a constant intensity, Etxebarria et al [59] demonstrated that the magnitude of the shift in MMSS is greater after a variable intensity exercise bout with multiple supramaximal surges in performance, even when both protocols are matched for total workload. A recent study with road cyclists showed similar results, with greater decrements in high-intensity performance following variable work [84]. Indeed, it has been hypothesized that while the absolute intensity of the surges is reduced throughout a race in MTB [13], it is possible that the efforts still represent the same relative intensity, as the intensity associated with the athlete's MMSS might have changed due to the work already performed.…”
Section: Impact Of a Variable Pacing Profile On Determinants Of Endur...mentioning
confidence: 72%
“…When compared to exercise performed at a constant intensity, Etxebarria et al [59] demonstrated that the magnitude of the shift in MMSS is greater after a variable intensity exercise bout with multiple supramaximal surges in performance, even when both protocols are matched for total workload. A recent study with road cyclists showed similar results, with greater decrements in high-intensity performance following variable work [84]. Indeed, it has been hypothesized that while the absolute intensity of the surges is reduced throughout a race in MTB [13], it is possible that the efforts still represent the same relative intensity, as the intensity associated with the athlete's MMSS might have changed due to the work already performed.…”
Section: Impact Of a Variable Pacing Profile On Determinants Of Endur...mentioning
confidence: 72%
“…When the individual TT performances are analyzed in relation to accumulated work (kJ/kg) or time spent above the lactate threshold (see Figure 5A,B), it appears that both factors may have influenced fatigue. However, considered in the context of recent work by Leo et al [11] and Spragg et al [13] and supported by correlation analysis on the individual data, showing a moderate correlation between the individual loss of TT power and time spent above LT1, it appears that intense work (time above LT1) rather than accumulated work is indicative of individual fatigue patterns [11][12][13]15]. It should be noted that statistical analyses also accounting for time above FTP or including an integrated Training Stress Score (TSS) index did not significantly strengthen the predicting power of individual fatigue patterns.…”
Section: Individual Fatigue Patternsmentioning
confidence: 99%
“…The importance of fatigue resilience is further supported by a case report by Gallo et al [10] with power analyses from three top-five Grand Tour (Giro d'Italia) finishers, indicating that the top contenders in the general classification in grand tours are able to sustain power output close to their personal best in prolonged efforts completed after 45 kJ/kg accumulated work. Although studies using retrospective analyses offer valuable insights into large datasets of power output in professional racing, they are limited in their ability to control whether the accumulated work is achieved through varied intensity distributions, different pacing strategies or tactical roles between athletes, or between shorter and longer races leading to different physiological stress and fatigue responses [7,[11][12][13]. Furthermore, observations from professional races limit the ability to include physiological measurements and conduct repeated maximal performance tests over the time course of the races, which would reduce confounding factors such as the tactical aspects and individual pacing strategies.…”
Section: Introductionmentioning
confidence: 99%